Acyl lipidation of a peptide: effects on activity and epidermal permeability in vitro - Rocco, D.; Ross, J.; Murray, P.; Caccetta, Rima (Dove Medical Press Ltd., 2016)
Short-chain lipid conjugates can increase permeability of a small peptide across human epidermis; however, the emerging lipoaminoacid (LAA) conjugation technique is costly and can deliver mixed synthetic products of varied biological potential. LAA conjugation using a racemic mixture produces a mixture of D- and L-stereoisomers. Individual enantiomers can be produced at an extra cost. We investigated an affordable technique that produces only one synthetic product: short-chain (C7–C8) acyl lipidation. Acyl lipidation of Ala-Ala-Pro-Val, an inhibitor of human neutrophil elastase (HNE; believed to lead to abnormal tissue destruction and disease development), was investigated as an alternative to LAA conjugation. The current study aimed to assess the effects of acyl lipidation (either at the N-terminal or at the C-terminal) on neutrophil elastase activity in vitro and on transdermal delivery ex vivo. The inhibitory capacity of the acyl conjugates was compared to LAA conjugates (conjugated at the N-terminal) of the same peptide. The L-stereoisomer appears to rapidly degrade, but it represents a significantly (P<0.05) better inhibitor of HNE than the parent peptide (Ala-Ala-Pro-Val). Although the D-stereoisomer appears to permeate human epidermal skin sections in a better fashion than the L-stereoisomer, it is not a significantly better inhibitor of HNE than the parent peptide. Acyl lipidation (with a C7 lipid chain) at either end of the peptide substantially enhances the permeability of the peptide across human skin epidermis as well as significantly (P<0.005) increases its elastase inhibitory potential. Therefore, our current study indicates that acyl lipidation of a peptide is a more economical and effective alternative to LAA conjugation.